Kepuasan Pengguna Rekam Medis Elektronik Melalui Pendekatan EUCS di RSI Sultan Agung - Rizqulloh, Lutfiyah; Putra, Ardy Nopiawan (Politeknik Negeri Jember, 2024)
Sultan Agung Islamic Hospital Semarang implemented RME gradually from 2019-2022 using SIMRS independently. However, in March 2023, the collaboration with a third party was not even a year old in early 2024 due to management changes; RME development was again carried out independently. The study aimed to evaluate user satisfaction with RME at RSI Sultan Agung Semarang using a cross-sectional design. The research sample comprised 32 respondents selected through purposive sampling: data collection with questionnaire instruments and descriptive data analysis. The results showed that the majority of respondents were satisfied with the RME system, with a percentage of satisfaction in the content aspect of 80.47%, accuracy of 77.05%, appearance of 73.21%, ease of use of 71.35%, and timeliness of 72.92%. All aspects fall into the excellent category, indicating that the RME system has met user needs. Further improvements need to be made to conduct periodic monitoring and evaluation of all aspects of the system and improve accuracy through a more rigorous data validation mechanism to meet user expectations and support more effective health services.